Effects of aging and lifelong aerobic exercise on basal and exercise-induced inflammation in women - Lavin, Kaleen M. (J Appl Physiol (1985), 2020)
Low muscle mass and frailty are especially prevalent in older women and may be accelerated by age-related inflammation. Habitual physical activity throughout the life span (lifelong exercise) may prevent muscle inflammation and associated pathologies, but this is unexplored in women. This investigation assessed basal and acute exercise-induced inflammation in three cohorts of women: young exercisers (YE, n = 10, 25 ± 1 yr, [Formula: see text]: 44 ± 2 mL/kg/min, quadriceps size: 59 ± 2 cm(2)), old healthy nonexercisers (OH, n = 10, 75 ± 1 yr, [Formula: see text]: 18 ± 1 mL/kg/min, quadriceps size: 40 ± 1 cm(2)), and lifelong aerobic exercisers with a 48 ± 2 yr aerobic training history (LLE, n = 7, 72 ± 2 yr, [Formula: see text]: 26 ± 2 mL/kg/min, quadriceps size: 42 ± 2 cm(2)). Resting serum IL-6, TNF-α, C-reactive protein (CRP), and IGF-1 were measured. Vastus lateralis muscle biopsies were obtained at rest (basal) and 4 h after an acute exercise challenge (3 × 10 reps, 70% 1-repetition maximum) to assess gene expression of cytokines (IL-6, TNF-α, IL-1β, IL-10, IL-4, IL-1Ra, TGF-β), chemokines (IL-8, MCP-1), cyclooxygenase enzymes (COX-1, COX-2), prostaglandin E(2) synthases (mPGES-1, cPGES) and receptors (EP3–4), and macrophage markers (CD16b, CD163), as well as basal macrophage abundance (CD68(+) cells). The older cohorts (LLE + OH combined) demonstrated higher muscle IL-6 and COX-1 (P ≤ 0.05) than YE, whereas LLE expressed lower muscle IL-1β (P ≤ 0.05 vs. OH). Acute exercise increased muscle IL-6 expression in YE only, whereas the older cohorts combined had the higher postexercise expression of IL-8 and TNF-α (P ≤ 0.05 vs. YE). Only LLE had increased postexercise expression of muscle IL-1β and MCP-1 (P ≤ 0.05 vs. preexercise). Thus, aging in women led to mild basal and exercise-induced inflammation that was unaffected by lifelong aerobic exercise, which may have implications for long-term function and adaptability. NEW & NOTEWORTHY We previously reported a positive effect of lifelong exercise on skeletal muscle inflammation in aging men. This parallel investigation in women revealed that lifelong exercise did not protect against age-related increases in circulating or muscle inflammation and that preparedness to handle loading stress was not preserved by lifelong exercise. Further investigation is necessary to understand why lifelong aerobic exercise may not confer the same anti-inflammatory benefits in women as it does in men.